Kajian Toeri Tentang Manajemen Risiko - Sherca Marcadia; Irsyad, Irsyad; Merika Setiawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Risk management is an approach designed to manage and minimize risks that are uncertain, have significant impacts, and have the potential to cause losses. The management process involves several steps, such as identifying risks, analyzing them, assessing the level of threat, and determining ways to control them. Risk itself is an inseparable part of human life, as every action always contains an element of uncertainty. Some experts even state that living without risk is as impossible as living without facing death. In general, risk is understood as the possibility of unexpected loss. (1) Risk indicates the likelihood of danger or loss arising from a particular event. (2) Risk also arises when there are various possible outcomes, but certainty cannot yet be determined.